Intergenerational neuroimaging study: mother–infant functional connectivity similarity and the role of infant and maternal factors. (28th November 2021) - Kim, Pilyoung; Chen, Haitao; Dufford, Alexander J; Tribble, Rebekah; Gilmore, John; Gao, Wei
Abstract: Mother and infant neural and behavioral synchrony is important for infant development during the first years of life. Recent studies also suggest that neural risk markers associated with parental psychopathology may be transmitted across generations before symptoms emerge in offspring. There is limited understanding of how early similarity in brain functioning between 2 generations emerges. In the current study, using functional magnetic resonance imaging, we examined the functional connectivity (FC) similarity between mothers and newborns during the first 3 months after the infant's birth. We found that FC similarity between mothers and infants increased as infant age increased. Furthermore, we examined whether maternal factors such as maternal socioeconomic status and prenatal maternal depressive symptoms may influence individual differences in FC similarity. For the whole-brain level, lower maternal education levels were associated with greater FC similarity. In previous literature, lower maternal education levels were associated with suboptimal cognitive and socioemotional development. Greater FC similarity may reflect that the infants develop their FC similarity prematurely, which may suboptimally influence their developmental outcomes in later ages.